(3aGVMI GdedMOjf hfGUMI GdehMOjfs - (3YdGA GdOjf GdHNGQj , eMeO Hf eMeO Hf eMeO GdHNGQj, YdGA GdOjf,J (B841 (3g` s
(3ChdgG (B:s
(3gPg QSGdI GdQO Ydi GdhLhOjI hQO CHGWjd cJGH GdaUhU eSeGI HaGVMI GdedMOjf hfGUMI GdehMOjf s
(3BNQgG (B:s
(3hNJe dXghQ GdSNW hGdNPdGf Ydi bdhH GdedMOjf hdPdc jUQahf Yf BjGJg hGdMeO ddg Ydi bdhH GdedMOjf hdPdc jUQahf Yf BjGJg hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B294s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1215s
Keywords: (3GdJhMjO hGdedd hGdfMds